'Essentially an American Institution Planted on Foreign Soil': The American Library in Paris, the Paris Herald, the Paris Tribune and Ex Libris. Issue 2 (October 2021) - Cannon, Nissa Ren
Abstract : In 1920, the American Library in Paris (ALP) was incorporated, with the desire to 'be a somewhat adequate representation of American life and thought' in the city. This paper will argue that the ALP - an institution established for overseas soldiers in 1918, which became its own entity in 1920 and celebrated a century of service in 2020 - would do more than represent America in the interwar period: it would play a role in shaping American identity as well. Through archival materials, this paper explores the ALP's representation in the three periodicals most imbricated with its interwar existence: the Paris editions of the Chicago Tribune and the New York Herald, and the little magazine, Ex Libris. I argue that the ALP - in both its physical and psychic forms - was an important site for the formation of transnational American identity in the interwar period, and that it strived to weigh in on conversations about emerging literary movements, including modernism and the Harlem Renaissance. American identity, as the Library represented it, combined national exceptionalism with a true desire for transnational cooperation. It was firmly at home on international soil, and well-versed in the era's literary debates.